Controlling factors of hydrocarbon accumulation and differential distribution in the western Qaidam Basin, Tibet Plateau. Issue 4 (19th May 2022) - Wu, H.; Zhang, Z.; Liu, S.; Wang, Z.; Zhuo, Q.; Lu, X.; Liu, H.
Abstract: Hydrocarbon distribution in the western Qaidam Basin is complex and characterised by large reserves, dispersed distribution, local enrichment, and multi-layer accumulation. Near the Altyn Tagh Ranges, the traps are mainly oil-filled, whereas far away and near the basin centre, they are gas-filled. With hydrocarbon distribution in the western Qaidam Basin poorly understood, the tectonic evolution, source-rock thermal evolution and space–time configurations were studied using burial history, strata thickness, source-rock generation and expulsion processes, and trap formation. Mode 1 system was characterised by continuous hydrocarbon accumulation, rapid source-rock burial and trap formation early in the basin history resulting in early generation and trapping of low maturity oil and later generation of high maturity oil. Mode 2 was characterised by mid-section hydrocarbon accumulation, steady source-rock burial velocity and trap formation with the traps filled by mature oil and small amounts of gas. Mode 3 was characterised by tail hydrocarbon accumulation, rapid source-rock burial and trap formation late in basin development resulting in traps filled with high-maturity gas. In the Mesozoic–Cenozoic petroleum system, such as the Dina2 condensate gas field, hydrocarbon accumulation was earlier than in the Yingxi Shizigou oilfield belonging to the Cenozoic petroleum system, which was mainly controlled by tectonic evolution and source-rock thermal evolution. The well-matching relationships between hydrocarbon generation–expulsion time and trap formation may create a giant oilfield, an earlier formed trap, later matured source rock and good preservation leading to continuous accumulation of hydrocarbon favourable for exploration. Key points: In the western Qaidam Basin, hydrocarbon differential distribution was mainly controlled by source-rock burial history, stratigraphic thickness and trap formation processes. Multi-stage hydrocarbon accumulation characteristics are classified into three modes according to the thermal evolution stage of the source rock. A comparison of hydrocarbon accumulation processes between the Yingxi oilfield in the western Qaidam Basin and Dina 2 gas fields in the Kuqa foreland basin allowed hydrocarbon accumulation modes to be determined.